Profesor Lazhar - Falardeau, Philippe; La Chenelière, Évelyne de, 1975- (A contracorriente films, 2012)
At a Montréal public grade school, an Algerian immigrant is hired to replace a popular teacher who committed suicide in her classroom. While helping his students deal with their grief, his own recent loss is revealed.